2006
DOI: 10.1002/ange.200503726
|View full text |Cite
|
Sign up to set email alerts
|

Die Chemie funktioneller Gruppen bei Organolithium‐Verbindungen: photochemische [2+2]‐Cycloaddition von Alkenyl‐substituierten Lithium‐Cyclopentadieniden

Abstract: Organolithium-Verbindungen gehören zu den wichtigsten Reagentien in der (metall)organischen Chemie.[1] Wegen der hohen Reaktivität und Empfindlichkeit dieser Verbindungen ist eine Chemie funktioneller Gruppen auf der Stufe der aktiven Organolithium-Nucleophile praktisch unbekannt. [2] Alle gewünschten Modifizierungen von funktionellen Gruppen in Synthesesequenzen müssen deshalb vor oder nach der Stufe der Organolithium-Reagentien durchgeführt werden. [3] Dies gilt auch für Synthesesequenzen, an denen substitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This study has shown that the parent bis(vinyl-Cp)zirconium dichloride complex ( 6 ) readily undergoes a photochemically induced intramolecular [2+2] cycloaddition reaction under our typical reaction conditions. This observation follows the general trend for this reaction type, as we have seen recently , that the outcome of this organometallic photocycloaddition is strongly dependent on the size and steric bulk of the α-substituent at the alkenyl unit. It seems to be a rule that small substituents (H, CH 3 ) at this position lead to a photostationary equilibrium that lies completely on the side of the ansa -metallocene isomer, whereas large cycloalkyl or aryl substituents may shift this equilibrium substantially, so that in these cases we often find mixtures of the open and ansa -metallocene isomers.…”
Section: Some Conclusionsupporting
confidence: 88%
“…This study has shown that the parent bis(vinyl-Cp)zirconium dichloride complex ( 6 ) readily undergoes a photochemically induced intramolecular [2+2] cycloaddition reaction under our typical reaction conditions. This observation follows the general trend for this reaction type, as we have seen recently , that the outcome of this organometallic photocycloaddition is strongly dependent on the size and steric bulk of the α-substituent at the alkenyl unit. It seems to be a rule that small substituents (H, CH 3 ) at this position lead to a photostationary equilibrium that lies completely on the side of the ansa -metallocene isomer, whereas large cycloalkyl or aryl substituents may shift this equilibrium substantially, so that in these cases we often find mixtures of the open and ansa -metallocene isomers.…”
Section: Some Conclusionsupporting
confidence: 88%
“…The conformationally rigid dienamine 120 can readily be obtained by Mannich coupling of acetyl groups at the ferrocene framework (Scheme 41). [61] Stoichiometric reaction of 120 a,b with the zwitterion 27 a gave an approximately 1:1 mixture of the mono(dihydrogen) and bis(dihydrogen) addition products 121 a,b and 122 a,b (see Schemes 41 and 42). [62] Experimental evidence indicates that 122 may originate from a slow subsequent hydrogenation reaction of 121 under the specific reaction conditions employed.…”
Section: Frustrated Lewis Pairsmentioning
confidence: 99%
“…[6] Intermediate A can be transformed into intermediates B-1 and B-2, with an equilibrium formed between all three anionic species. [7] When enone 2a (MVK) is used as the electrophile, enolate C-1 is formed by Michael addition of intermediate B-2 to 2a, which subsequently reacts with sulfonated imine 3 to give the corresponding cascade addition product 4, presumably because the lithiated sp 3 carbanion prefers this Michael addition (Scheme 2). The other addition products 5 and 7-10 were also obtained via the intermediates B-1 and B-2, in accord with our previously reported results.…”
Section: Resultsmentioning
confidence: 99%